Low cost biopolymer-silica hybrid adsorbent - Wan Norfazilah, Wan Ismail; Annur Isma Husna, Mohd Ismail; Hartina, Mohd Yusop (2021)
Adsorbent - simple operation and implementation, low cost, high performance efficient regeneration and eco-friendly operating system. Biopolymer-based hybrid adsorbents - highly biodegradable and widely available. Inulin (biopolymer) - cheap, versatility, biocompatible, water soluble carbohydrate, non-toxic, hydrophilic and biodegradable. TEOS (precursor) - non-toxic and cheap. High adsorption capacity with surface area of 17.69 m²/g, pore size of 2-50 nm (mesoporous) and pore volume of 0.02 cm³/g.